PERAN MOTIVASI, DISIPLIN KERJA TERHADAP KOMITMEN KARYAWAN DAN KINERJA KARYAWAN PADA PERUSAHAAN AIR MINUM DI MALANG RAYA - Liana, Yuyuk; Irawati, Rina (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
The purpose of this study was to examine the direct effect of motivation, discipline to organizational commitment, and examine the effect of indirect motivation, discipline on performance through organizational commitment. The sample was 150 employees of PDAM Malang which is using simple random sampling. The research proves that there is a significant influence between motivation, organizational commitment and discipline to performance. While the indirect effect of motivation on performance through organizational commitment results obtained by (P1 X P3) = 0.477 x 0.159 = 0.0758, whereas the indirect influence between disciplines working on performance through organizational commitment is equal to (P2 x P4) = 0.186 x 0.199 = 0.0370. It conclude that the greatest influence is indirect effect of motivation on performance through organizational commitment. Keywords: motivation, discipline, organizational commitment, performance.